2001
DOI: 10.1086/322537
|View full text |Cite
|
Sign up to set email alerts
|

IUE Absorption‐Line Observations of the Moderately and Highly Ionized Interstellar Medium toward 164 Early‐Type Stars

Abstract: We present measurements of Galactic interstellar Al III, Si IV, and C IV absorption recorded in highresolution archival ultraviolet spectra of 164 hot early-type stars observed by the International Ultraviolet Explorer (IUE) satellite. The objects studied were drawn from the list of hot stars scheduled to be observed with the Far Ultraviolet Spectroscopic Explorer (FUSE) satellite as part of observing programs designed to investigate absorption by O VI in the Galactic disk and halo. Multiple IUE echelle-mode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
12

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 89 publications
12
49
12
Order By: Relevance
“…It was assigned different spectral types and luminosity classes in the past, ranging from O9 to B3 and from II to V. The most recent classification is the one given by Mathys (1988): O9.5 III. Savage et al (2001) reported the spectroscopic parallax distance d ¼ 2740 pc, with an accuracy estimated to be about 30% (i.e., about 800 pc here). This value is in good agreement with the one reported by Diplas & Savage (1994), d ¼ 2716 pc.…”
Section: The Targetmentioning
confidence: 58%
“…It was assigned different spectral types and luminosity classes in the past, ranging from O9 to B3 and from II to V. The most recent classification is the one given by Mathys (1988): O9.5 III. Savage et al (2001) reported the spectroscopic parallax distance d ¼ 2740 pc, with an accuracy estimated to be about 30% (i.e., about 800 pc here). This value is in good agreement with the one reported by Diplas & Savage (1994), d ¼ 2716 pc.…”
Section: The Targetmentioning
confidence: 58%
“…We then focused on kinematic evidence for feedback. In the ISM, enhancements in velocity width are found in regions of higher than average SFRs such as Orion (Cowie, Songaila, & York 1979) and Carina (Walborn et al 1998;Savage, Meade, & Sembach 2001). Evidently, gas in these regions is stirred up by increased supernova activity.…”
Section: Search For Evidence Of Star Formation and Feedbackmentioning
confidence: 99%
“…Typically the profile widths of CIV, SiIV and NV absorption lines have been found to be quite broad in the general interstellar medium (b > 10 km s −1 ), indicating their origin in high temperature, often collisionally ionized regions (Savage et al 2001). However, we have found surprisingly small values (<4.5 km s −1 ) for the doppler b-values for the CIV and NV absorption component seen at V ∼ −1.0 km s −1 towards HD 127381.…”
Section: Interstellar Absorption Towards Hd 128345 Andmentioning
confidence: 99%